Limb Preservation with Balloon Angioplasty in Critical Limb Threatening Ischemia: A Case Report - Imelda Krisnasari; Novi Kurnianingsih; Mohammad Saifur Rohman; Budi Satrijo; Anna Fuji Rahimah (Heart Science Journal, 2021)
AbstractIntroduction Chronic limb-threatening ischemia (CLTI) is a syndrome represents the end stage of peripheral artery disease (PAD). PAD increased the risk of major amputation and cardiovascular events. The initial treatment approach for CLTI may significantly impact the risk of major amputation or death.Case Description A hypertensive 72-years old female complained left leg pain followed with wound on her left toe since 4 months ago. The wound persist although her toe was already amputated. On physical examination, the pulsation was diminished in her left pedis. Duplex ultrasound showed monophasic spectral doppler from left popliteal artery to distal left anterior tibial artery (ATA) and distal posterior tibial artery (PTA). CT-Angiography showed short total occlusion (2cm) at the distal left Superficial Femoral artery (SFA), multiple stenosis with maximal 90% stenosis at the left ATA and chronic total occlusion at the proximal-mid left posterior tibial artery (PTA). She was diagnosed with CLTI left inferior extremity Fontaine IV Rutherford 5. Angiography result was similar to CT-angiography result. The patient was successfully treated with plain balloon angioplasty from distal left SFA to distal left ATA and also drug coated balloon angioplasty from the distal left SFA to popliteal artery. Her wound also consulted to surgical department.Conclusion Appropriate revascularization is a fundamental to limb preservation. The option of strategy based on anatomical characterization and WIfI stage. We successfully perform endovascular strategy with TIMI flow 3 from left SFA to distal left TA and also distal PTA in our patient but we still need further holistic CLTI management.